Modern Solutions For Economic Higher Education In The Knowledge-Based Society - Paul Pocatilu; Cristian Ciurea (Amfiteatru Economic Journal, 2011)
The use of modern solutions specific to contemporary society, together with stakeholders' involvement, will lead to a substantial increase in the practice-oriented approach of the teaching process. The objective of this paper is to present directions for the implementation of modern teaching solutions in the economic higher education. It highlights the implications that knowledge-based economy brings for the economic higher education. It analyzes the virtual campus as a modern solution for collaborative higher education and the level of knowledge in the use of mobile devices and technologies in the learning process of students from three faculties of the Academy of Economic Studies. The analysis is based on a survey conducted among students enrolled in three faculties of the Bucharest Academy of Economic Studies. A series of indicators is proposed to assess the efficiency of human resources training activities, developed in order to enhance the relevance of economic higher education for the labor market and knowledge-based society. The research results consist in identifying modern solutions for the use of mobile technologies by students in the educational process.
Keywords: D83; I21; 330; knowledge society; higher education; e-learning; m-learning; information technology